2017
DOI: 10.1159/000480256
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Function during Repeated TACE Procedures and Prognosis after Introducing Sorafenib in Patients with Unresectable Hepatocellular Carcinoma: Multicenter Analysis

Abstract: Background/Aim: We evaluated the relationship of hepatic function with repeated transarterial catheter chemoembolization (TACE) and prognosis after sorafenib treatment in various patient cohorts. Methods: Study 1 comprised of 212 Barcelona clinic liver cancer stage-B (BCLC-B) HCC patients classified as Child-Pugh A (CP-A) and who had received repeated TACE treatments (r-TACE) (naïve:recurrence = 66:146). Study 2 comprised of 435 patients with unresectable HCC classified as CP-A in who sorafenib was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 41 publications
2
128
0
1
Order By: Relevance
“…In our previous study, hepatic function worsened with repeated TACE procedures [43] , as determined with the use of the newly proposed ALBI score [44][45][46] . Some reports have noted the usefulness of ALBI grade for patients undergoing sorafenib treatment and for subclassification of BCLC-B HCC [47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, hepatic function worsened with repeated TACE procedures [43] , as determined with the use of the newly proposed ALBI score [44][45][46] . Some reports have noted the usefulness of ALBI grade for patients undergoing sorafenib treatment and for subclassification of BCLC-B HCC [47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
“…The first-line treatment for patients with intermediate-stage HCC is transcatheter arterial chemoembolization (TACE); however, the release of large concentrations of angiogenic factors, such as vascular endothelial growth factor (VEGF), triggered by hypoxia induced by TACE results in tumor progression and recurrence [3-5]. Another disadvantage of TACE is that repeated procedures reduce liver function [6]; therefore, minimizing the number of TACE sessions is a critical challenge in the treatment of intermediate-stage HCC patients. Several clinical trials have attempted to address this problem by combining TACE with molecular targeted agents; however, to date, all have ended in failure [7-11], and the combination of TACE and molecular targeted agents is therefore not recommended in routine practice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ALBI grade has been reported to have a better assessment ability for obtaining good hepatic reserve function in treated patients [10, 14, 27, 28]. Among the present 115 naïve HCC patients who had multiple countable tumors (≤5) and unmet needs, hepatic function in the Comb group was worse as compared to that in the SR group when assessed by ALBI grade (ALBI grade 1: 42.4 vs. 64.6%, p = 0.034) as well as Fib-4 index (6.30 ± 5.34 vs. 3.75 ± 2.10, p = 0.019), whereas OS and DFS rates were not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among the present 115 naïve HCC patients who had multiple countable tumors (≤5) and unmet needs, hepatic function in the Comb group was worse as compared to that in the SR group when assessed by ALBI grade (ALBI grade 1: 42.4 vs. 64.6%, p = 0.034) as well as Fib-4 index (6.30 ± 5.34 vs. 3.75 ± 2.10, p = 0.019), whereas OS and DFS rates were not significantly different between the groups. In previous studies, ALBI grade has shown better prognostic predictive value as compared to Child-Pugh class for various therapeutic modalities, including surgical resection [29, 30], RFA [31, 32], TACE [33], and sorafenib [28], as well as in ALBI-T [14] and mALBI-T [10, 11] scores as total scoring systems. Clinical unmet needs such as those seen in our patients might be resolved by complementary use of low invasive RFA in combination with resection.…”
Section: Discussionmentioning
confidence: 99%